The Influence of Primordialism and Social Media on Voter Behavior In Kampar District Elections for The 2017-2022 Period (Case Study in Tambang District) - Rudi Rahman (Formosa Journal of Multidisciplinary Research, 2023)
The background of this research is the weak socialization of the government and the lack of campaigning for each pair of regent and deputy regent candidates, the weak level of people accessing social media related to news of the regional head election in Kampar district, and the behavior of voters when making choices based on ethnicity from their place of origin. . This study aims to, firstly, determine the effect of social media on voter behavior, secondly, to determine the effect of primordialism on voter behavior and thirdly, to determine the effect of social media and primordialism on voter behavior in the 2017-2022 Kampar district head election in Tambang sub-district. The research design uses survey research using a questionnaire as a tool for collecting data. The research population is the residents of Rimbo Panjang and Tarai Bangun Village. The research sample was 28,197 people with the sampling technique using a multistate random sampling technique. The data analysis technique uses multiple linear regression with data processing using the SPSS 17.0 program. The results showed that the t-test showed that there was an influence between social media (X1) on voter behavior (Y) with a value of tcount≥ttable or 57.304> 2.58 meaning that H1 was accepted, there was an influence of primordialism (X2) on voter behavior (Y) with value 101.536> 2.58, while H3 with the F test (ANOVA test) shows that there is the influence of social media and primordialism on voter behavior (H3) 6932.802> 0.305.